2010
DOI: 10.5539/ijbm.v5n6p3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leadership styles on four variables of executives workforce

Abstract: Leadership is widely considered to be an important aspect of organizing and there are several reasons to suggest that managerial styles are of particular relevance in this context. However, there is a dearth of both theoretical and empirical work on leadership styles and their subsequent effects on middle managers' organizational commitment, their job satisfaction, their communication and their managerial effectiveness. The aim of this paper is to report the findings of an empirical study exploring the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(15 reference statements)
1
8
0
3
Order By: Relevance
“…Hasil penelitian ini mendukung pendapat bahwa dengan dorongan dan inspirasi maka pemimpin harus memiliki gaya kepemimpinan yang dapat memberikan contoh kerja yang baik sehingga terjadi peningkatan efektivitas kerja (Dubrin, 2013). Sedangkan hasil penelitian sebelumnya yang relevan, menyatakan bahwa gaya kepemimpinan memiliki pengaruh positif langsung terhadap efektivitas kerja (Galanou, 2010). Gaya kepemimpinan direplikasi dalam sikap dan perilaku namun pada gilirannya inilah hasil interaksi kompleks antara cara berpikir dan nuansa individu (Khan & Nawaz, 2016).…”
Section: Pengujian Hipotesisunclassified
“…Hasil penelitian ini mendukung pendapat bahwa dengan dorongan dan inspirasi maka pemimpin harus memiliki gaya kepemimpinan yang dapat memberikan contoh kerja yang baik sehingga terjadi peningkatan efektivitas kerja (Dubrin, 2013). Sedangkan hasil penelitian sebelumnya yang relevan, menyatakan bahwa gaya kepemimpinan memiliki pengaruh positif langsung terhadap efektivitas kerja (Galanou, 2010). Gaya kepemimpinan direplikasi dalam sikap dan perilaku namun pada gilirannya inilah hasil interaksi kompleks antara cara berpikir dan nuansa individu (Khan & Nawaz, 2016).…”
Section: Pengujian Hipotesisunclassified
“…Barbuto Jr, et al (2007) found that older leaders were considered to be more transformational in their leadership style, and that those with an advanced degree were also perceived by their employees as having a transformational style. However, the importance of examining both the personal and the organizational dimensions of leadership style is also recognized (Galanou, 2010); the current study seeks to address this issue through its focus on micro and small businesses.…”
Section: Gender and Entrepreneurial Leadershipmentioning
confidence: 99%
“…Those employee who are not satisfied will look for ways to exit their current organization and find better working conditions that satisfy the. (GALANOU, 2010) stated that in the case that a dissatisfied employee is unable to find a better alternative, they will not be cooperative with the management and not be connected to the organization at an intrinsic level despite continuing to work there. Many researchers like (Kinnie, Hutchinson, Purcell, Rayton, & Swart, 2005) concluded that there was a significant relationship between the level of job satisfaction and the outcomes.…”
Section: Definitions Of Key Conceptsmentioning
confidence: 99%